2017
DOI: 10.1111/vsu.12731
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in margin length after excision of grade II mast cell tumors and grade I and II soft tissue sarcomas in dogs

Abstract: Objective: Quantify changes in the circumferential lengths of surgical margins of resected canine mast cell tumors (MCT) and soft tissue sarcomas (STS) between the time of collection and histopathology.Study design: Prospective, hypothesis-driven, clinical study.Sample population: Two hundred and thirty-seven margins from 69 excised tumors (50 MCT and 19 STS) in 51 client-owned dogs. Methods:The lengths of surgical margins were recorded (eg, cranial, caudal, dorsal, and ventral) for each tumor at 5 time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Shrinkage of the tumour specimens can result in tumour cells being closer to the surgical resection margins than in vivo. The majority of this specimen shrinkage occurs immediately after surgical resection because of the effects of myofibril contractility and tissue elasticity following release from adjacent tissues . In one study of 216 canine tumour specimens, the total overall shrinkage was 15.6% with 13.7% shrinkage occurring immediately after surgical resection and only 1.7% after formalin fixation .…”
Section: Residual (R) Tumour Classification Schemementioning
confidence: 99%
See 3 more Smart Citations
“…Shrinkage of the tumour specimens can result in tumour cells being closer to the surgical resection margins than in vivo. The majority of this specimen shrinkage occurs immediately after surgical resection because of the effects of myofibril contractility and tissue elasticity following release from adjacent tissues . In one study of 216 canine tumour specimens, the total overall shrinkage was 15.6% with 13.7% shrinkage occurring immediately after surgical resection and only 1.7% after formalin fixation .…”
Section: Residual (R) Tumour Classification Schemementioning
confidence: 99%
“…In one study of 19 resected canine cutaneous MCTs, the overall specimen shrinkage was 17.7% with 24.4% shrinkage in the grossly normal adjacent skin and only 4.5% shrinkage in the tumour . Other studies have also found a significant effect of both histologic processing and biologic factors, such as tumour infiltration into the grossly normal surgical margin, on shrinkage of specimens . Regardless, specimen shrinkage will result in HTFMs being less than the true tumour‐free margins obtained during surgery.…”
Section: Residual (R) Tumour Classification Schemementioning
confidence: 99%
See 2 more Smart Citations
“…Histologic safety margins have not been defined in veterinary oncology and are infrequently described in human oncology 24 . There is also inherent imprecision within a quantified surgical margin, as the measured margin reduces at each stage of processing following surgery (in vivo, ex vivo, postfixation, subgross, when mounted on glass) before a final assessment of the histologically tumor‐free margin, 32 with a mean length reduction ranging from 35% to 42% 33 . The greater interobserver percentage agreement in histological reporting when the R scheme was used compared to the ≤1 mm scheme (83% vs 68%), demonstrates the benefit of an objective method of histological margin reporting and merits further investigation in prospective studies.…”
Section: Discussionmentioning
confidence: 99%